EFEKTIVITAS TEKNOLOGI DIGITAL DALAM PEMBELAJARAN ANAK BERKEBUTUHAN KHUSUS: SLR - Puput Ambaryuni; Liftiah Liftiah; Ali Formen (STKIP Subang, 2026)
Technological advances have made a significant contribution to supporting the learning process for children with special needs (ABK). Various digital media have begun to be used to help improve students' motivation to learn, communication skills, focus, and understanding of learning materials. However, the effectiveness of digital technology utilization in ABK learning still requires further study through various previous research results. This study aims to assess the effectiveness of digital technology in learning for children with special needs using the SLR method. The research process was carried out by collecting and reviewing relevant scientific articles from various sources, such as Google Scholar. The research stages included searching for articles, selecting them based on certain criteria, analyzing data, and compiling a synthesis of research results. The study results indicate that the use of digital technology, such as interactive multimedia, learning videos, and educational applications, can improve the motivation, interaction, and learning outcomes of students with special needs. In addition to helping students, digital technology also supports teachers in creating more flexible and tailored learning to their needs. However, the implementation of digital technology still faces several obstacles, including limited facilities, teachers' ability to utilize technology, and access to digital devices. Therefore, it is necessary to provide support for infrastructure, training for educators, and the development of appropriate learning media so that the use of digital technology in learning for children with special needs